Beyond Prostate-Specific Antigen: New Serologic Biomarkers for Improved Diagnosis and Management of Prostate Cancer - Shariat, Shahrokh F (MedReviews, LLC, 2004)
The use of total prostate-specific antigen (tPSA) measurement has dramatically improved the ability to detect prostate cancer at earlier stages. However, as the number of men presenting with advanced disease (and high tPSA levels) has decreased, and given the fact that tPSA is highly reflective of benign prostatic hyperplasia, the need has emerged for novel biomarkers specifically associated with prostate cancer in order to improve predictive models. Several new biomarkers have shown promise, and studies continue to investigate the role of these markers in the detection, staging, and prognosis of prostate cancer. As new useful biomarkers continue to emerge, guidelines for their employment, as well as coordination of further research studies, are needed; a systematic, phased, nomogram-based model is a rational way to manage these efforts.